Correlations between the activity of sensory neurons and behavior: how much do they tell us about a neuron’s causality? - Nienborg, Hendrikje (2010)
How the activity of sensory neurons elicits perceptions and guides behavior is central to our understanding of the brain and is a subject of intense investigation in neuroscience. Correlations between the activity of sensory neurons and behavior have been widely observed and are sometimes used to infer how neurons are used to guide a certain behavior. This view is challenged by 1) theoretical considerations that these correlations rely on the existence of correlated noise and its structure, and 2) recent empirical observations suggesting that such correlated noise is not a fixed network property but that it depends on various sources, and varies with a subject’s mental state.